2021
DOI: 10.3390/sports9100139
|View full text |Cite
|
Sign up to set email alerts
|

Relative Training Load and Match Outcome: Are Professional Soccer Players Actually Undertrained during the In-Season?

Abstract: Previous studies examined training/match ratios (TMr) to determine the training load relative to the match load, but the influence of the relative training load (RTL) on success in soccer is still unknown. Therefore, this study aimed to investigate the possible influence of RTL on final match outcome in soccer (win, draw, and loss). Running performances (RP) of soccer players (n = 21) in the Croatian highest national soccer competition were analyzed during the season 2020–2021. Data were measured by the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Such findings are fully in line with previous research, which reported smaller effect sizes in higher speed categories [ 23 ]. Authors of this research explained that smaller effect sizes were associated with HIR due to the low absolute values of HIR (i.e., compared to TD and low-intensity running) during the matches [ 23 ], which was well-described in previous research investigating MRP [ 10 , 11 , 49 , 50 ]. Other results from the current study could directly support such findings.…”
Section: Discussionmentioning
confidence: 92%
“…Such findings are fully in line with previous research, which reported smaller effect sizes in higher speed categories [ 23 ]. Authors of this research explained that smaller effect sizes were associated with HIR due to the low absolute values of HIR (i.e., compared to TD and low-intensity running) during the matches [ 23 ], which was well-described in previous research investigating MRP [ 10 , 11 , 49 , 50 ]. Other results from the current study could directly support such findings.…”
Section: Discussionmentioning
confidence: 92%
“…These results are in agreement with Clemente et al ( 2019a ) and Modric et al ( 2021b ), who demonstrated that through weekly training sessions, the TDC and accelerations/decelerations were more emphasized than the high-intensity distance covered (e.g., VHSRD and SpD). According to Modric et al ( 2021a ), training approaches usually contain drills that are performed in small areas, players are limited in reaching higher running speeds. As a consequence of not being exposed to high intensity running patterns, players mostly do not meet the loads imposed during matches.…”
Section: Discussionmentioning
confidence: 99%
“…are performed. Grünbichler et al ( 2020 ), based on an microcycle composed of 5 training sessions, MD-5 to MD-1, suggest that for an optimal pre-match preparation, coaches should plan sprint (>7.0m/s) training session during the week (3–4 days before the match) and additionally should avoid excessive training loads and long sessions 1 day before the match, while Modric et al ( 2021a ), with the same type of weekly schedule, indicate that players should be exposed to a minimum of 75–80% of the high-intensity running (>5.5 m/s) normally characterizing a match in the middle of the week, as well as training methodology that utilizes a “high-volume and low-intensity” training session in the second day after the match (i.e., on MD-5) may positively impact success in soccer. Although there are trends and similarities in the management of daily loads during the microcycle, this management must be unique, situational, and evolutionary to meet the needs of the team and the players, as a group and individuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soccer requires a combination of aerobic and high-intensity demands (e.g., sprints, changes of direction) (Barnes et al, 2014;Bush et al, 2015), which defines the match running performance among professional soccer players (Modric et al, 2022;Modric, Versic, et al, 2021). Indeed, these demands during training sessions may also determine the outcomes of matches (Modric, Jelicic, et al, 2021). A common method to assess these demands in soccer players is the Yo-Yo intermittent recovery test (Yo-Yo IRT) (Castagna et al, 2020;Deprez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%